Management of High Ankle Sprains Utilizing the Tightrope Surgical Procedure – A Novel Approach for a Rapid Return to Play - Michael L. Voight; Connor Norman; Kevin E. Wilk; Matthew Lucas; Chris Wolfe (International Journal of Sports Physical Therapy)
The distal tibiofibular joint is described as a syndesmosis. The syndesmosis is important to the structural integrity of the ankle joint by maintaining the proximity of the tibia, fibula, and talus. Syndesmotic or high ankle sprains, involving the syndesmotic ligaments, pose a significant rehabilitative challenge due to their intricate anatomy, prolonged recovery periods following injury, and high susceptibility to persistent disability. Traditional management strategies have often been conservative, marked by lengthy periods of immobilization and a gradual return to activity. Severe syndesmotic injuries with diastasis have been treated surgically with screw fixation which may require a second intervention to remove the hardware and carries an inherent risk of breaking the screw during rehabilitation. Another fixation technique, the Tightrope™, has gained popularity in treating ankle syndesmosis injuries. The TightRope™ involves inserting Fiberwire® through the tibia and fibula, which allows for stabilization of the ankle mortise and normal range of motion. The accelerated rehabilitation protocol promotes early weight-bearing and has been shown to expedite the return to sport. This emerging strategy has shown promise in reducing recovery time as it is now possible to return to sport in less than 2 months after a tightrope repair and accelerated rehabilitation, compared with 3–6 months post screw fixation. This clinical commentary delves into this novel approach, highlighting the procedure, rehabilitation protocols, and the implications for physical therapy practice.